2020
DOI: 10.11144/javeriana.rgps19.sspp
|View full text |Cite
|
Sign up to set email alerts
|

Situación de salud de la población privada de la libertad en Colombia. Una revisión sistemática de la literatura

Abstract: Las personas privadas de la libertad (PPL) están sujetas a condiciones adversas para su salud y problemas estructurales en los diferentes establecimientos penitenciarios y carcelarios (EPC) que restringen su resolución. Objetivo: analizar la evidencia científica que permita comprender la situación de salud de las PPL del país. Método: se realizó una revisión sistemática de las investigaciones en salud realizadas en las prisiones de Colombia, en algunas bases de datos y literatura gris, con los siguientes térmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…The serological analysis in our study showed very complete data for infections of HBV, HCV and HIV, which exceeded the data obtained in other studies [44][45][46]. The prevalence of HIV and HCV is greater for inmates than the general population [47].…”
Section: Discussioncontrasting
confidence: 65%
“…The serological analysis in our study showed very complete data for infections of HBV, HCV and HIV, which exceeded the data obtained in other studies [44][45][46]. The prevalence of HIV and HCV is greater for inmates than the general population [47].…”
Section: Discussioncontrasting
confidence: 65%
“…The PDL were considered one of the highest risk groups in the coronavirus pandemic, in part, due to the unfavorable conditions they experienced before their detention, such as social segregation, poverty, marginalization and exclusion, as well as punitive criminal policies that favored overcrowding 5,9 . These conditions imposed significant challenges in the management of prison guidelines to reduce the spread of the virus, following WHO recommendations 5 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), SARS-CoV-2 has become a global public health crisis [2][3][4] , with 701.168.995 million cases globally, including 110.309.712 in the United States and 6.387.145 in Colombia, with 143,110 registered deaths in this country 5,6 . Although the mortality rates have decreased, there is still a latent risk of reinfection 7 and vulnerable and marginalized populations will be the most affected 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Desde entidades como la Procuraduría General de la Nación, se percibe ausencia de atención psicosocial por motivo de la pandemia hacia la población privada de la libertad. Esta manifestó la necesidad de apoyo psicológico como aspecto coyuntural en los momentos de pandemia, similar a la urgencia vivida por la población privada de la libertad expresada en Barrenger y Bond (2021) y López Hernández (2020), y recordaron la necesidad de fortalecimiento de programas para el tratamiento penitenciario, aun en medio de la emergencia. En esta línea, percibieron la ausencia de personal, por ejemplo, los practicantes del área de psicología, como producto de las medidas adoptadas para mitigación del contagio.…”
Section: Respuesta Psicológica ¿Dónde Están Las Buenas Compañías Cuan...unclassified